Entrepreneurship Training and Performance of Small and Micro Enterprises in Information Communication Technology Sector in Nairobi City County, Kenya - Nganu, Margaret (My University, 2018)
Entrepreneurship training has been identified as a major contributor to small and micro enterprises’ skills development and performance. Several studies have been carried out in Kenya to establish the relationship between entrepreneurship training and performance. However, these studies are general and do not distinguishing the nature of the relationships. Moreover, there lacks sufficient evidence on the specific roles played by training needs assessment, content of training and method of training as factors of entrepreneurship training on performance. The general objective of this study was to investigate the influence of entrepreneurship training on performance of small and micro enterprises in Information Communication Technology sector in Nairobi City County. The specific objectives were; to establish the extent to which training needs assessment; content of training; and training methods influence performance of small and micro enterprises in the Information Communication Technology sector and the extent to which business characteristics moderate the relationship between entrepreneurship training and performance of small and micro enterprises in the Information Communication Technology sector. The study was based on economic development theory; entrepreneurial self-efficacy and intentions theory; social cognitive theory; training needs assessment theory; and balanced scorecard model. The study adopted a positivist research philosophy. Mixed method research design was used to collect qualitative and quantitative data. The target population for this study was 273 small and micro enterprises in the Information Communication Technology sector that successfully received entrepreneurship training prior to the year 2012 under the Information Communication Technology Authority. Systematic random sampling technique was used to select 73 respondents. Two sets of semi-structured questionnaires were used to collect primary data. Document analysis was done to collect secondary data. Content validity of the instrument was evaluated using literature and experts opinions, while construct validity was assessed through factor analysis. The instrument’s reliability was measured by Cronbach’s Alpha. Prior to analysis, diagnostic tests were carried out. Normal probability plots and Shapiro –Wilk test were used for normality test. Variance inflation factor was used to test multicollinearity. Quantitative data was analyzed using descriptive and inferential statistics. Descriptive statistics incorporated absolute percentages, frequencies, measures of central tendency (mean, mode, median) and measures of dispersion (standard deviation); while inferential statistics was analyzed through correlation and regression analysis to establish the nature and magnitude of the relationships between the variables and tested the hypothesized relationships. Qualitative data collected from the open-ended questions was analyzed through content analysis. The study established positive influence of training needs assessments and content of training on small and micro enterprises in Information Communication Technology sector in Nairobi City County, Kenya. The method of training had an insignificant relationship with business performance. The study revealed that lecture method was mostly used during trainings and trainees preferred discussions or participatory methods. This study indicated that business characteristics statistically significantly moderate the relationship between entrepreneurship training and firm performance. That is, as age of the business, size of the business and education level of the owner of the business increases, the more positive impact the entrepreneurship training has on firm performance. The study recommends that trainers should conduct training needs assessments before conducting entrepreneurship trainings. Trainers should give equitable emphasis on entrepreneurial skills, managerial skills, and technical skills training. Still, trainers need to review their training methods in line with the training needs and the trainees’ expectations. Finally, the government needs to regulate and broaden the curriculum of entrepreneurship training